Non-catalytic pyrolysis of ethane to ethylene in the presence of CO2 with or without limited O-2 - Choudhary, Vasant R.; Mondal, Kartick C.; Mulla, Shafeek Abdul Rashid (Journal of Chemical Science, 2006)
Influence of the presence Of CO2, which is a mild oxidant, on the performance of the thermal cracking of ethane to ethylene in the absence or presence of limited O-2 at different temperatures (750-900 degrees C), space velocities (1500-9000 h(-1)) and CO2/C2H6 and O-2/C2H6 mole ratios (0-2.0 and 0-0.3 respectively) has been investigated. In both the presence and absence of limited 02, ethane conversion increases markedly because of the presence Of CO2, indicating its beneficial effect on the ethane to ethylene cracking. The increased ethane conversion is, however, not due to the oxidation of ethane to ethylene by CO2; the formation of carbon monoxide in the presence Of CO2 is found to be very small. It is most probably due to the activation of ethane in the presence Of CO2.
Keywords: ethane; ethane cracking in presence Of CO2; ethane cracking in presence of CO2 and limited O-2; Ethylene; thermal cracking of ethane

Selective oxidation of ethane over Mo-V-Al-O oxide catalysts: insight to the factors affecting the selectivity of ethylene and acetic acid and structure-activity correlation studies - Sankaranarayanan, T. M.; Ingle, Rohit H.; Gaikwad, T. B.; Lokhande, S. K.; Raja, T.; Devi, R. N.; Ramaswamy, V.; Manikandan, Palanichamy (Catalysis Letters, 2008)
Catalysts of general formula, MoVAlOx were prepared with the initial elemental composition of 1:0.34:0.167 (Mo:V:Al) at a pH value in the range of 1-4. The elemental analysis showed that the final composition of the catalysts is pH dependant. The performance of the catalysts was tested for selective oxidation of ethane to give ethylene and acetic acid. While all of them were active for ethane oxidation with a moderate conversion, the catalyst prepared at pH 2 showed a highest activity with 23% ethane conversion and a combined selectivity of 80.6% to ethylene and acetic acid. The catalyst prepared at pH 4 was least selective to ethylene and acetic acid. Various techniques like powder XRD, SEM, Raman, UV-Vis and EPR were used to characterize the catalysts and to identify the active phases responsible for the selective oxidation of ethane. The powder XRD data showed that the catalysts prepared at pH 1 and 2 contain mainly of MoO3 and MoV2O8 along with traces of Mo4O11. The amount of MoO3 was slightly higher in the catalyst prepared at pH 1. However, the catalyst prepared at pH 3 contains mainly of MoV2O8 with no trace of MoO3. The catalyst prepared at pH 4 showed V2O5 as the major phase along with MoVAlO4 phase. The Raman data corroborated the XRD results. EPR and UV-Vis studies indicated the presence of traces of V-4 in pH 1 and 2 catalysts and significant amount of Mo5+ in all the catalysts. Thus, the high activity and selectivity to ethylene and acetic acid are attributed to the presence of MoV2O8 phase and other reduced species like Mo4O11 phase supported on MoO3. The presence of V and Mo ions in a partially reduced form seems to play a crucial role in the selective oxidation of ethane.
Keywords: Acetic acid; ethane; Ethylene; mixed metal oxide; Selective oxidation

Ammonia clathrate hydrates as new solid phases for Titan, Enceladus, and other planetary systems - Shin, Kyuchul; Kumar, Rajnish; Udachin, Konstantin A.; Alavi, Saman; Ripmeester, John A. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
There is interest in the role of ammonia on Saturn's moons Titan and Enceladus as the presence of water, methane, and ammonia under temperature and pressure conditions of the surface and interior make these moons rich environments for the study of phases formed by these materials. Ammonia is known to form solid hemi-, mono-, and dihydrate crystal phases under conditions consistent with the surface of Titan and Enceladus, but has also been assigned a role as water-ice antifreeze and methane hydrate inhibitor which is thought to contribute to the outgassing of methane clathrate hydrates into these moons' atmospheres. Here we show, through direct synthesis from solution and vapor deposition experiments under conditions consistent with extraterrestrial planetary atmospheres, that ammonia forms clathrate hydrates and participates synergistically in clathrate hydrate formation in the presence of methane gas at low temperatures. The binary structure II tetrahydrofuran + ammonia, structure I ammonia, and binary structure I ammonia + methane clathrate hydrate phases synthesized have been characterized by X-ray diffraction, molecular dynamics simulation, and Raman spectroscopy methods.
Keywords: ethane; hydrate inhibitors; hydrogen bonding; ice; single crystal X-ray diffraction

Healable network polymers bearing flexible poly(Lauryl Methacrylate) chains via thermo-reversible furan-maleimide diels-alder reaction - Patil, Sachin S.; Torris, Arun; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
A new ATRP initiator containing two furyl rings, namely, bis(furan-2-ylmethyl) 2-bromopentanedioate was synthesized starting from commercially available L-glutamic acid as a precursor. Well-defined bisfuryl-terminated poly(lauryl methacrylate) macromonomers with molecular weight and dispersity in the range 5000-12,000 g mol(-1) and 1.30-1.37, respectively, were synthesized employing the initiator by atom transfer radical polymerization (ATRP). Independently, 1,1',1"(nitrilotris(ethane-2,1-diyl)) tris(1H-pyrrole-2,5-dione) was synthesized as a tris-maleimide counterpart for furan-maleimide click reaction. Thermo-reversible network polymer bearing flexible poly(lauryl methacrylate; (PLMA) chains was obtained by furan-maleimide Diels-Alder click reaction of bisfurylterminated PLMA with 1,1',1"-(nitrilotris(ethane-2,1-diyl)) tris(1Hpyrrole-2,5-dione). The prepared network polymer showed retro-Diels-Alder reaction in the temperature range 110-170 degrees C as determined from DSC analysis. The presence of low Tg (-40 degrees C) PLMA chains induced chain mobility to the network structure which led to the complete scratch healing of the coating at 60 degrees C in five days due to furan-maleimide adduct formation. The storage modulus of the network polymer was found to be 3.7 x 10(4) Pa at the constant angular frequency of 5 rad/ sec and strain of 0.5%. The regular reversal of storage (G0) and loss modulus (G") was observed with repeated heating (40 to 110 degrees C) and cooling cycles (110 to 40 degrees C) at constant angular frequency and strain. (C) 2017 Wiley Periodicals, Inc.
Keywords: ethane; Monomers; polymerization